LEGAL RECONSTRUCTION OF CORRUPTION ACT IN INDONESIA TO. REALIZE A JUST LAW ENFORCEMENT - QOHAR AF., ABDUL (Jurnal Independent, 2022)
Abstract In detail, the assets recovery bill provides for the confiscation of assets in terms of (1). The suspect or defendant has died, fled, is permanently ill, or his whereabouts are unknown; or (2). The defendant was released from all lawsuits. For the confiscation of assets from both of them, it can also be carried out against assets whose criminal cases cannot be tried or have been found guilty by a court that has obtained permanent legal force, and later it is found out that there are assets from the criminal activities that have not been declared confiscated. As for the confiscation of assets, it does not apply to improper assets that will be confiscated. Confiscation of Assets does not eliminate the power to prosecute the perpetrator of a criminal act. Assets confiscated based on a court decision that has obtained legal force can still be used to prosecute the perpetrator of a criminal act.